Liveable Lives - Banerjea, Niharika; Browne, Kath (Bloomsbury Academic, 2023)
Liveable Lives examines what makes life liveable for LGBTQ+ people beyond equality reforms. It refuses the colonizing narrative of surviving in a ‘regressive’ Global South and thriving in a ‘progressive’ Global North. By linking the concept of liveability with the decolonial literature on sexualities, this open access book draws on individual's stories, art and writing to examine how lives become liveable across India and the UK, providing a multifaceted investigation of two divergent contexts where activists refuse local framings of exclusion/inclusion and LGBTQ+ lives are continually re-envisioned. Embracing diverse methodologies, including workshops, in-depth interviews, street theatres, and web surveys, the book stands as an example of a queer collaborative praxis that refuses the familiar Global North / Global South practices of theorizing and data gathering. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on www.bloomsburycollections.com.